Effect of Tumor Location on Clinicopathological and Molecular Markers in Colorectal Cancer in Eastern China Patients: An Analysis of 2,356 Cases - Song, Yaolin; Wang, Lili; Ran, Wenwen; Li, Guangqi; Xiao, Yujing; Wang, Xiaonan; Zhang, Li; Xing, Xiaoming (Frontiers in Genetics, 2020)
Colorectal cancer (CRC) has become a major health concern in China due to its increasing incidence and mortality. This study aimed to clarify the relation between tumor locations and the clinicopathological, molecular marker features in eastern China CRC patients. We continuously collected data on 2,356 cases of CRC who underwent surgical resection from January 2017 to April 2019. Right-sided colorectal cancer (RCC), was located from the cecum to the transverse colon and left-side colorectal cancer (LCRC) was located from the splenic flexure to rectum. The clinicopathological indices (including age, sex, pTNM stage, mucinous production, and distant metastasis) and frequencies of molecular markers such as KRAS, NRAS, BRAF, and microsatellite instability (MSI) were statistically analyzed between RCC and LCRC groups. The associations between clinicopathological characters and molecular markers were also investigated. LCRC and RCC proportions in eastern China CRC patients were 81.75% and 18.25%, respectively. RCC (vs. LCRC) was more frequently observed with higher frequencies of MSI-high (MSI-H) and BRAF mutation in female, younger patients, and was closely associated with metastasis, poor differentiation, and mucinous tumors. Tumor location also showed significant differences in bowel wall infiltration degree and pTNM stage. Mutation rates of KRAS, NRAS, MSI, and BRAF were 40.15%, 3.85%, 6.31%, and 2.30%, respectively. Patients with KRAS mutation tended to be female, had mucinous, perineural invasive, and polypoid tumor. Those with NRAS mutation tended to develop well-differentiated ulcerative tumors. BRAF mutation was more relevant with lymph node involvement, deeper infiltration of bowel wall, mucinous, poorly-differentiated tumor with thrombus, and perineural invasion. Furthermore, MSI-H was more commonly found in younger patients with deeper bowel wall infiltration and poorly-differentiated polypoid tumor, whereas MSS patients tended to develop lymph node involvement, and mucinous and perineural invasive tumor. In our study, we found that LCRC and RCC showed different features on the clinicopathological and molecular markers in eastern China CRC patients. Since our data differ from those of the Western countries and other regions in China, further studies are required to clarify the regional differences of the clinicopathological and molecular markers in CRC patients.